Flow photochemistry — from microreactors to large-scale processing. (March 2023) - Zhang, Mengxue; Roth, Philippe
Abstract : Miniaturized continuous photoreactors have been recently receiving an increasing amount of attention from researchers both in academia and in industry. The upscaling of flow photoreactors without compromising the reactor performances, however, remains a major challenge for large-scale processes. This review provides an overview of existing commercial flow photoreactors, and the scaling-up strategies of photochemical processes using commercial flow reactors or in-house-fabricated reactors with recent illustrated examples. The strategies to upscale flow photoreactors will be discussed as well as the design principles. In addition, the topic of reactor characterization will be mentioned alongside the selection of the most relevant parameter to lead to a pertinent comparison across scales.